Delivering best care and maintaining emotional wellbeing in the intensive care unit: the perspective of experienced nurses - Siffleet, Jo; Williams, A.; Rapley, Pat; Slatyer, Susan (2015)
Aim - This study explored the perspective of experienced intensive care nurses regarding maintenance of their emotional wellbeing. Background - Caring for critically ill patients has been identified as stressful. The demand for critical care nurses continues to grow in a climate of an ongoing nursing shortage and an aging workforce. This study sought to understand what environmental elements optimized the maintenance of emotional wellbeing. Methods - Grounded theory. Results - Fifteen experienced intensive care unit registered nurses from a metropolitan hospital in Western Australia, were interviewed. Five categories were identified: ‘achieving best care’, ‘caring for the patient's family’, ‘autonomy within the ICU environment’, ‘teamwork’, and ‘previous nursing and life experience’. Conclusions - The findings from this study increase our understanding of the environmental elements that can optimize the emotional wellbeing of intensive care nurses. These findings will assist in the development of strategies to retain nurses in the ICU area.